MEDIATION AND JUDICIARY IN ITALY 2019 - Matteucci, Giovanni (Revista Eletrônica de Direito Processual, 2019)
According to the European Parliament (12.9.2017) “Italy uses mediation at a rate six times higher than the rest of Europe”. Mandatory mediation was ruled in 2010 in Italy and came in force in 2011. Furious opposition by lawyers, benign neglect by judges. In 2013 the “Opt-Out” model was introduced. Results: year 2011 - 60,810 mediation proceedings, 9,912 agreements, 16% success rate. year 2018 - 151,923 mediation proceedings, 20,965 agreements, 14% success rate.20,965 is the highest number of agreements through mediation ever reached in Italy. If all parties were present and they decided to go beyond the first meeting, the success rate in 2018 was 45%. Nevertheless, mediation is growing well below its potential: 3.220,928 new proceedings were filed in courts in 2018. The Italian judges con order the litigants to undergo a mediation (delegated mediation) (ex art. 5, c.2, D.Lgs. 28/2010) or / and make a solution proposal based on equity (ex art. 185-bis civil procedure code), which the parties are free to accept or refuse (not binding arbitration), in all subjects related to alienable civil rights. When compulsory mediation was ruled they looked at mediation with a "benign neglect”, but since 2015 it is thanks to the judiciary that the use of mediation has been increasing in Italy: mediation proceedings delegated by judges were 2% (of all incoming mediation procedures) in 2011, 10% in 2015, 11% in 2016, 13% in 2017, 15% in 2018